ANALISIS MODEL PELUANG BERTAHAN HIDUP (SURVIVAL) DAN APLIKASINYA - S. FAJARIYAH; H. SUMARNO; N. K. K. ARDANA (MILANG Journal of Mathematics and Its Applications, 2013)
Up till now, models of demography mathematics usually use discrete approximation. This research will use continue approximation agree with demography characteristic that always change every times.  The Maximum Likelihood method is chosen by using five distributions. There are two data that use i.e. hypothetic data and life table data of Banten. The result of hypothetic data shows that if we choose real distribution, it will produce the good value of 2 R , whereas with survival data of Banten. The result shows that Weibull distribution is the best from another distributions. Keywords: survival function, maximum likelihood method.